Non-native parasitic copepod Neoergasilus japonicus (Harada, 1930) utilizes non-native fish host Lepomis gibbosus (L.) in the floodplain of the River Dyje (Danube basin) - Ondračková, Markéta; Fojtů, Jitka; Seifertová, Mária; Kvach, Yurii; Jurajda, Pavel (Parasitology research, 2019)
The parasitic copepod Neoergasilus japonicus (Harada, 1930) (Ergasilidae), native to east Asia, is widely distributed in Asia, Europe, and North and Central America. Recently, this species appeared in lentic water bodies of the River Dyje floodplain (Danube basin, Czech Republic). It was first recorded in 2015 and in 2 years it reached a 100% prevalence in recently expanding non-native fish host, Lepomis gibbosus (Linnaeus, 1758) (Centrarchidae, native to North America) at two borrow pits. Abundance of N. japonicus increased with fish length, with maximum intensity of infection reaching 99 parasites per fish. The parasite was most frequently found attached to the dorsal and anal fins of fish, while preference for the dorsal fin was more evident with lower infection intensities. Utilization of expanding fish hosts in water bodies that are regularly interconnected via natural or managed flooding may support the rapid dispersal of this non-native parasite.
Keywords: Fish Diseases; Copepoda; Animals; Copepod; zavlečené druhy; ploutve zvířat; nemoci ryb; Centrarchidae; Neoergasilus; infestace ektoparazity; Česká republika; Czech Republic; Female; Rivers; Introduced Species; ženské pohlaví; Lepomis; zvířata; řeky; Animal Fins; Ectoparasitic Infestations; Species introductions; 18S, 28S rDNA; Perciformes